Africa Climate Mobility Academy (ACMA) 1 year anniversary 2025 - Bioversity International And International Center For Tropical Agriculture (CIAT) (2025)
10 young African scholars arrived with ideas, questions, and a shared goal: to understand how climate shapes human movement across the continent. Through intensive workshops, 800+ mentorship hours, and field visits in Busia County, Kenya, these fellows turned ideas into actionable insights for policy. Over the last year, 9 fellows have submitted to peer-reviewed journals, and 75% remain active in our growing alumni network. By investing in mentorship and local institutions, CGIAR Climate Security and partners are addressing global inequalities in who produces climate impact research and whose voices shape solutions.